Semantic Relationships and their Impact on the Harmony of the Qur’an Text (The Qur’an Interpretation Books for the Fifth Hijri Century as a Model) - Resea. Firdaus Abdul Wahid Shakir; Dr . Mahmoud Hammoud Arak (Journal of College of Education, 2024)
Semantic relationships are one of the important tools in textual linguistics. Because of its clear effect on the interconnection of sentences and texts, and I followed the sayings of the scholars of interpretation in the fifth century AH, balanced between what they mentioned and what the textualists said.     And it turns out that hermeneutics scholars have referred to the semantic relationships between the texts, and showed their types. Because textual relationships with conceptual interconnectedness are renewed with texts, so that almost every text creates its semantic coherence methods, “and these relationships ... are what help us link the references in the text to each other, and help us to develop and transform them so that they are in the end a strong thread that connects the text with an invisible bond. To kindness to reveal it.
Keywords: Semantic relationships, text, coherence, Quranic exegesis books